Diagnostic Role of Chromosomal Instability in Melanoma - Nitika Dabas; Diana M. Byrnes; Ashley M. Rosa; Mark S. Eller; James M. Grichnik (Journal of Skin Cancer)
Early diagnosis gives melanoma patients the best chance for long term survival. However discrimination of an early melanoma from an unusual/atypical benign nevus can represent a significant challenge. There are no current pathological markers to definitively define malignant potential in these indeterminate lesions. Thus, there is a need for improved diagnostic tools. Chromosomal instability (CIN) is a hallmark of cancer and is markedly prevalent in melanoma. Advances in genomics have opened the door for the development of molecular tools to better segregate benign and malignant lesions. This paper focuses on CIN in melanoma and the role of current diagnostic approaches.